Inhibition of basal and glucagon-induced hepatic glucose production by 991 and other pharmacological AMPK activators. Issue 12 (30th June 2022) - Johanns, Manuel; Corbet, Cyril; Jacobs, Roxane; Drappier, Melissa; Bommer, Guido T.; Herinckx, Gaëtan; Vertommen, Didier; Tajeddine, Nicolas; Young, David; Messens, Joris; Feron, Olivier; Steinberg, Gregory R.; et al.
Abstract : Pharmacological AMPK activation represents an attractive approach for the treatment of type 2 diabetes (T2D). AMPK activation increases skeletal muscle glucose uptake, but there is controversy as to whether AMPK activation also inhibits hepatic glucose production (HGP) and pharmacological AMPK activators can have off-target effects that contribute to their anti-diabetic properties. The main aim was to investigate the effects of 991 and other direct AMPK activators on HGP and determine whether the observed effects were AMPK-dependent. In incubated hepatocytes, 991 substantially decreased gluconeogenesis from lactate, pyruvate and glycerol, but not from other substrates. Hepatocytes from AMPKβ1 −/− mice had substantially reduced liver AMPK activity, yet the inhibition of glucose production by 991 persisted. Also, the glucose-lowering effect of 991 was still seen in AMPKβ1 −/− mice subjected to an intraperitoneal pyruvate tolerance test. The AMPK-independent mechanism by which 991 treatment decreased gluconeogenesis could be explained by inhibition of mitochondrial pyruvate uptake and inhibition of mitochondrial sn -glycerol-3-phosphate dehydrogenase-2. However, 991 and new-generation direct small-molecule AMPK activators antagonized glucagon-induced gluconeogenesis in an AMPK-dependent manner. Our studies support the notion that direct pharmacological activation of hepatic AMPK as well as inhibition of pyruvate uptake could be an option for the treatment of T2D-linked hyperglycemia.